Historical Roots of the Formation of Concepts of Professions in Preschool Children - Shakhlo Sattarova (Genius Journals, 2022)
This article describes the historical roots of the formation of ideas about professions among preschoolers. The article also summarizes opinions on the coverage of vocational education in folk oral and written sources
Keywords: folklore; written sources; child; profession